New records of Lubens lubens (Braun, 1901) and Pojmanskia riosae Zamparo, Brooks & Causey, 2003 (Digenea) in Taraba major (Vieillot) (Aves: Thamnophilidae) from Argentina - Lunaschi de Redolatti, Lía Inés (2014)
Pojmanskia riosae (Digenea: Leucochloridiidae) and Lubens lubens (Digenea: Dicrocoeliidae) are described from the intestine and cloaca of the Chororó or Great Antshrike, Taraba major (Passeriformes: Thamnophilidae) from Formosa Province, Argentina. The finding of P. riosae constitutes the first record of the genus for South American birds and the first record in thamnophilid birds. The discovery of L. lubens in T. major represents a new host record and the first report of this species in Argentina. Moreover, Lubens phelpsi is synonymized with L. lubens.